Long-term acidification of urine in patients treated for infected renal stones - Wall, I; Tiselius, H G (Urologia internationalis, 1990)
The effects of ammonium chloride, methenamine hippurate and ascorbic acid on urinary pH was studied in 14 normal subjects. A statistically significant reduction of urinary pH was recorded with ammonium chloride in daily doses of 1.5 and 3 g, but not with 2 g of methenamine hippurate or 1.8 g of ascorbic acid. Long-term treatment with ammonium chloride in doses between 1.5 and 3 g was given to 11 patients in order to reduce the risk of new stone formation or growth of fragments remaining after disintegration of infected renal stones. Biochemical stone analyses showed struvite in 9 of the treated stones, and urine cultures verified the presence of urease-producing bacteria in 10 patients. Apart from ammonium chloride, the patients were treated with antibiotics, in 4 patients continuously and in the others during periods from 2 to 34 months. The patients were followed for an average period of 32 months. No adverse reactions were recorded with the dosage used. Initially, 6 patients were stone-free, whereas 5 had residual stone fragments with a largest diameter ranging from 4 to 20 mm. At follow-up, 2 patients were still stone-free, and of 5 patients with residual fragments 1 showed stable disease and 3 an improved stone situation. In 5 patients, 3 of whom had residual stone fragments, antibiotic treatment had been interrupted without infectious relapse.